Development and initial validation of a novel smoothed‐particle hydrodynamics‐based simulation model of trabecular bone penetration by metallic implants. Issue 4 (16th November 2017) - Kulper, Sloan A.; Fang, Christian X.; Ren, Xiaodan; Guo, Margaret; Sze, Kam Y.; Leung, Frankie K. L.; Lu, William W.
ABSTRACT: A novel computational model of implant migration in trabecular bone was developed using smoothed‐particle hydrodynamics (SPH), and an initial validation was performed via correlation with experimental data. Six fresh‐frozen human cadaveric specimens measuring 10 × 10 × 20 mm were extracted from the proximal femurs of female donors (mean age of 82 years, range 75–90, BV/TV ratios between 17.88% and 30.49%). These specimens were then penetrated under axial loading to a depth of 10 mm with 5 mm diameter cylindrical indenters bearing either flat or sharp/conical tip designs similar to blunt and self‐tapping cancellous screws, assigned in a random manner. SPH models were constructed based on microCT scans (17.33 µm) of the cadaveric specimens. Two initial specimens were used for calibration of material model parameters. The remaining four specimens were then simulated in silico using identical material model parameters. Peak forces varied between 92.0 and 365.0 N in the experiments, and 115.5–352.2 N in the SPH simulations. The concordance correlation coefficient between experimental and simulated pairs was 0.888, with a 95%CI of 0.8832–0.8926, a Pearson ρ (precision) value of 0.9396, and a bias correction factor Cb (accuracy) value of 0.945. Patterns of bone compaction were qualitatively similar; both experimental and simulated flat‐tipped indenters produced dense regions of compacted material adjacent to the advancing face of the indenter, while sharp‐tipped indenters deposited compacted material along their peripheries. Simulations based on SPH can produce accurate predictions of trabecular bone penetration that are useful for characterizing implant performance under high‐strain loading conditions. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:1114–1123, 2018.